Mediamorfosis Edukasi Informal Online Melalui Platform Digital Sebagai Peluang Bisnis Baru - Endah Fantini; Rousdy Safari Tamba (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The existence of digital and online-based technology has supported disruption in society. This also changed the dynamics of the education business to be able to change the development of digitalization which became a milestone in the Industrial Revolution 4.0. The existence of formal education is starting to become popular because today's learning media is very easy to obtain through Video On Demand on the internet. Although now more and more are offering informal education with the virtual learning model. Although not a few, take advantage of this opportunity to provide informal education for new business opportunities. Through Mediamorfosis Theory, here the researchers found that the convergence of informal education has changed the pattern of learning that is related to technical expertise for audiences who have a high level of activity. Besides, this informal study also provides official certificates approved by the institution, so that the potential, business too, formality, informal, and informal.